Empiricist Epistemology as the Foundation for the Acquisition of Knowledge Through Sensory Experience in the Development of Modern Science - Ibnul Amin (Integrated Education Journal, 2025)
Empiricist epistemology is a major school of thought in the philosophy of knowledge that emphasizes that the primary source of human knowledge comes from sensory experience. This school of thought developed rapidly in the Western world, especially in the modern era, as a reaction to rationalism, which prioritizes reason as the source of knowledge. Figures such as John Locke, George Berkeley, and David Hume were central figures in shaping the foundations of empiricism. This paper discusses the definition of empiricism, its key figures, its basic concepts, and its influence on the development of modern science.